Segmented handle assembly for agricultural tools. - Hussain, Hasnul Hadi; Salman, Nur Qamarina; Abd. Ghani, Kamarul Zaidi; Kamaludin, Ahmad Rodhi; Ismail, Nor Haiman Shah; Che Jid, Muhd Rizal; Mohamad Shapie, Mohd Faiz; Mohamad Darus, Mohamad Harlizan (2010)

(untitled)
The present invention provides a segmented handle assembly preferably used in conjunction with farming/agricultural tools, that comprises of a plurality individual segments of predefined lengths whereby each individual segment that make up the handle, have at one end a cylindrical cavity that forms a female connector that is further threaded by a helical thread and at the other symmetrically opposing end a complementarity threaded male connector. The entire handle assembly is assembled by means of screwing each of the plurality of segments. The farming/agricultural tool itself is attached to the assembled handle in a similar manner. The entire assembly (the complete handle assembly and the farming/agricultural tool) is locked against disassembly after a complete initial assembly by means of bolting with the aid of screws via a bore-hole and perforation combination that are located on the male and female connectors of the plurality of handle segments. The screws are secured transversely to the longitudinal orientation of the handle assembly.